(untitled) (Neo Science Peer Reviewed Journal, 2023)
Mirza Ulughbek ibn Shahrukh Mirza (1394-1449) enthusiastic and highly influential activity in the field of science and first of all in his branch like astronomy became and remains his greatest and greatest service to all mankind. Another of his great services is the construction of huge construction works of scientific-educational (madrasa) and scientific-research (observatory) buildings. In this regard, Ulug’bek demonstrated his high abilities as an excellent organizer of research work and a great scholar of his time, leaving an indelible mark on the pages of history. He established a real academy in Samarkand. The academy had a well-equipped observatory, a rich library and a madrasa, the highest educational institution of its time. Information about the activities of the Ulugbek madrasa is also given in the sources related to the history of Sufism created at that time. An example of this can be the works written on the life and work of representatives of the Khojagon-Naqshbandiya sect. However, hagiographical works, that is, stories about the lives and activities of great religious and public figures and religious leaders, as well as their merits, were hardly studied during the Soviet era.